Search for standard model production of four top quarks in proton-proton collisions at root s=13TeV - Sirunyan, A. M. (2017)
A search for events containing four top quarks (t (t) over bart (t) over bar) is reported from proton-proton collisions recorded by the CMS experiment at root s = 13 TeV and corresponding to an integrated luminosity of 2.6 fb(-1). The analysis considers the single-lepton (e or mu)+jets and the opposite-sign dilepton (mu(+)mu(-),mu +/- e -/+ , or e(+) e(-))+ jets channels. It uses boosted decision trees to combine information on the global event and jet properties to distinguish between t (t) over bart (t) over bar and t (t) over bar production. The number of events observed after all selection requirements is consistent with expectations from background and standard model signal predictions, and an upper limit is set on the cross section for t (t) over bart (t) over bar production in the standard model of 94 fb at 95% confidence level (10.2 x the prediction), with an expected limit of 118 fb. This is combined with the results from the published CMS search in the same-sign dilepton channel, resulting in an improved limit of 69 fb at 95% confidence level (7.4xthe prediction), with an expected limit of 71 fb. These are the strongest constraints on the rate of t (t) over bart (t) over bar production to date. (C) 2017 The Author(s). Published by Elsevier B.V.